How Dell reformed its supply chain technology to reduce risk - Gallien, Jérémie (Henry Stewart Talks, 2016)
The case study reviews how Dell, the technology company, overhauled its supply chain systems to reduce shortages and enable desktop computers to be delivered more efficiently from arrival at port to destinations in the US.